Improving the convergence properties of the moving-mesh code AREPO - Pakmor, Rüdiger; Springel, Volker; Bauer, Andreas; Mocz, Philip; Munoz, Diego J.; Ohlmann, Sebastian T.; Schaal, Kevin; Zhu, Chenchong (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. Accurate numerical solutions of the equations of hydrodynamics play an ever more important role in many fields of astrophysics. In this work, we rein
Published online 2015
Gesehen am 23.10.2020